HVEM Promotes the Osteogenesis of allo-MSCs by Inhibiting the Secretion of IL-17 and IFN-γ in Vγ4T Cells - Lei He; Jun Xiao; Lei Song; Rui Zhou; Zhigang Rong; Weifeng He; Fei Dai (Frontiers in Immunology, 2021)
Bone defects are a common orthopaedic concern, and an increasing number of tissue-engineered bones (TEBs) are used to repair bone defects. Allogeneic mesenchymal stem cells (allo-MSCs) are used as seed cells in many approaches to develop TEB constructs, but the immune response caused by allogeneic transplantation may lead to transplant failure. V gamma 4 T (Vγ4T) cells play an important role in mediating the immune response in the early stage after transplantation; therefore, we wanted to verify whether suppressing Vγ4T cells by herpesvirus entry mediator (HVEM)/B and T lymphocyte attenuator (BTLA) signalling can promote MSCs osteogenesis in the transplanted area. In vitro experiments showed that the osteogenic differentiation of MSCs and Vγ4T cells was weakened after co-culture, and an increase in interleukin-17 (IL-17) and interferon-γ (IFN-γ) levels was detected in the culture supernatant. HVEM-transfected MSCs (MSCs-HVEM) still exhibited osteogenic differentiation activity after co-culture with Vγ4T cells, and the levels of IL-17 and IFN-γ in the co-culture supernatant were significantly reduced. In vivo experiments revealed that inflammation in the transplanted area was reduced and osteogenic repair was enhanced after Vγ4T cells were removed. MSCs-HVEM can also consistently contribute to reduced inflammation in the transplanted area and enhanced bone repair in wild-type (WT) mice. Therefore, our experiments verified that HVEM can promote the osteogenesis of allo-MSCs by inhibiting IL-17 and IFN-γ secretion from Vγ4T cells.